Four spot megrim (Lepidorhombus boscii) weight-length and weight-weight relationships in northern Iberian waters (stock 8.c, 9.a) - Landa, Jorge; Fontenla-Giráldez, Jorge; Reparaz, María; Castro-Loehmann, Begoña; Gancedo, Rosa María; Rodríguez-Fernández, Lorena; Loureiro-Caride, María Isabel; Gómez-González, Antonio (2022)
Total weight-length, gutted weight-length and total weight-gutted weight relationships were fitted for the Iberian Atlantic stock of four spot megrim (Lepidorhombus boscii) and their temporal variations were analyzed. The large sample size, size range and timeseries available allowed obtaining robust somatic parameters of combined sexes for the total weight-length relationships (a=0.0043, b=3.2008), for the gutted weight-length relationships (a=0.0055, b=3.1139), and the weight conversion factors (1.062). They are considered to best fit the current biometric relationships and most appropriate to be used in the stock assessment of the status of the stock and they contribute to a deeper knowledge of the life history traits of this species. BIOBENTON-4 Biología de especies bentónicas comerciales (rape blanco, rape negro, gallo del norte, gallo, cigala y cuco) en el área del ICES